25 More than meets the eye: Parental perspectives on the health of their extremely preterm children when they reach 18 months, 5 and 7 years. (19th August 2020) - Duquette, Laurie-Anne; Luu, Thuy Mai; Janvier, Annie; Mai-Vo, Thuy-An; Fortin, Aurelie; Thivierge, Emilie; Bourque, Claude Julie; Pearce, Rebecca; Synnes, Anne; Jaworski, Magdalena
Abstract: Background: Extremely preterm birth is associated with death and a higher risk of adverse long-term outcomes. Neurodevelopmental impairment (NDI) has become the focus of neonatal follow-up and outcome research, with classifications chosen by clinicians and researchers. However, parents were never consulted about this classification. Objectives: To examine parental perspectives about the health of their ex-preterm infants. Design/Methods: Over a one-year period, at Sainte-Justine University Hospital's Neonatal Follow-Up Clinic, all parents of children born <29 weeks' gestational age, aged between 18 months corrected age and 7 years were approached. They were asked two questions: " Please rate your child's health from your point of view on a scale from 0 (very poor) to 10 (excellent )" and " If you could improve up to two things about your child's health and/or development, what would they be? " Responses were analyzed using mixed methods. Results: 249 parental responses were obtained (98% participation rate). On average, parents rated their child's health to be 8/10 (range 3-10/10, median 8/10). Main themes invoked about areas for improvement were developmental outcomes (65%):" if he could talk and hold his head up himself "; respiratory heath and overall medical fragility (35%): " improve the health of her lungs "; and behavior/emotional issues (21%): " his anxiety ". Twenty-three percent did not wish to improve anything: " I am very happy with his health and development. I hope he continues on the same path." When examining developmental outcomes more closely, the recurrent sub-themes for improvement were: language/communication (22%), motor/movement (17%) and cognitive/learning (16%): " improving her attention in school" . Conclusion: When they come to neonatal follow-up, parents generally perceive the health of their extremely preterm children in a positive way. While some parents have no wishes for improvement in their children, many are concerned by their children's NDI. On the other hand, several parent-important outcomes, such as lung health and overall medical fragility, are insufficiently investigated during follow-up at the present time.